Bending tests of delignified and densified poplar. Issue 1 (2nd January 2023) - Wehsener, Jörg; Bremer, Martina; Haller, Peer; Fischer, Steffen
ABSTRACT: Wood modification has a long tradition to improve durability and other properties. In this study, a combination of delignification and densification to enhance bending strength and ASE (anti-swelling efficiency) was introduced. Both treatments change the properties of modified wood in different ways depending on the conditions and species. The objective of this treatment combination was the improvement of mechanical properties by partly extracting lignin. The treated structure retains the alignment of cellulose and hemicellulose chains. The densification perpendicular to the grain reduced the cell lumina and compressed the wood structure by more than 70%. As a result, the cell walls become decreased entangled and new hydrogen bonds between adjacent cellulose nanofibres were linked. The combined processes were applied to the green and dried poplar ( Populus nigra L.). Firstly: the delignification procedure was done with small specimens in NaOH and Na2 SO3 solution at 100°C, 130°C or 150°C for 7 h. After washing and analysing wood components densification followed. The wood was compressed 80% perpendicular to the grain in different temperatures (100°C, 130°C, 160°C) and pressing times (4, 20, 24 h) of the original thickness. After the treatment, ASE and bending strength (MoR, MoE) were determined. The bending strength was meanly dependent on the solution temperature and compression time and temperature. Bending strength will increase up to 450 MPa and has the optimum at around 90% lignin removal and 130°C pressing time over 24 h. ASE was reduced by strong delignification and increasing temperature.